2019
DOI: 10.12998/wjcc.v7.i12.1499
|View full text |Cite
|
Sign up to set email alerts
|

Removal of pediatric stage IV neuroblastoma by robot-assisted laparoscopy: A case report and literature review

Abstract: BACKGROUND Neuroblastoma (NB) is the most common extracranial solid tumor in children, with an incidence of approximately 1/10000. Surgical resection is an effective treatment for children with NB. Robot-assisted laparoscopic surgery is a new method and is superior to conventional laparoscopic surgery, since it has been preliminarily applied in clinical practice with a significant curative effect. This paper discusses significance and feasibility of complete resection of stage IV NB using robot-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Despite this, there does exist a wide range of literature mostly in the form of individual case reports or small case series. One case of successful robotic resection of a stage IV neuoroblastoma has been reported, with the authors noting that the enhanced vision and precision of the robotic platform allowed for skeletalisation of tumour vasculature that may not have been feasible laparoscopically [61]. Another case described the management of a 4 cm juvenile cystic adenomyoma by a robotic approach in a 15-year-old girl, with improved ergonomics allowing for four-layered closure of the uterus, followed by an uneventful post-operative recovery [62].…”
Section: Surgical Oncologymentioning
confidence: 99%
See 1 more Smart Citation
“…Despite this, there does exist a wide range of literature mostly in the form of individual case reports or small case series. One case of successful robotic resection of a stage IV neuoroblastoma has been reported, with the authors noting that the enhanced vision and precision of the robotic platform allowed for skeletalisation of tumour vasculature that may not have been feasible laparoscopically [61]. Another case described the management of a 4 cm juvenile cystic adenomyoma by a robotic approach in a 15-year-old girl, with improved ergonomics allowing for four-layered closure of the uterus, followed by an uneventful post-operative recovery [62].…”
Section: Surgical Oncologymentioning
confidence: 99%
“…A common theme discussed in many of these cases is the advantages offered by a robotic approach to extended lymph node dissection resulting from enhanced 3-dimensional vision [13,[61][62][63][64]. A recent case series of 12 robotic resections of paediatric abdominal tumours concluded that oncological surgical principles were maintained by this approach, with all achieving R0 resection status, low postoperative morbidity and good long-term results.…”
Section: Surgical Oncologymentioning
confidence: 99%
“…Complete resection is curative in low-stage disease. Robotic surgery can skeletonize abdominal blood vessels in the tumor and cut the tumor into pieces, including stage IV retroperitoneal neuroblastoma [155,156].…”
Section: Abdominal Tumorsmentioning
confidence: 99%
“…The latest guidelines from the National Comprehensive Cancer Network and the European Society of Gynecological Oncology suggest that open surgery and laparoscopic surgery (using traditional laparoscopic or robotic techniques) are the main surgical approaches for radical hysterectomy for patients with stage IA2-IIA cervical cancer[7-9]. Robotic surgery has been increasingly used in abdominal surgery and has shown more beneficial effects[10-12].…”
Section: Introductionmentioning
confidence: 99%